Efficacy of Online Versus Offline Group Exercise Program in Knee Osteoarthritis: A Randomized Controlled Trial - Agnihotri, Saurabh; Singh, Naveen Kumar; Gupta, Nalina (Asian Journal of Medical Research, 2025)
Background: Knee osteoarthritis (OA) is a leading cause of pain and disability among older adults. Exercise therapy is a primary non-pharmacological intervention for managing OA symptoms. With the rise of digital health platforms, the effectiveness of online rehabilitation programs compared to traditional offline exercise requires further evaluation. Objective: To compare the efficacy of online versus offline group exercise programs in reducing pain, as measured by the Visual Analogue Scale (VAS), in patients with knee osteoarthritis. Subjects and Methods: This randomized controlled trial included 160 participants with radiographically confirmed Grade I–III knee OA. Participants were randomized to either an online (n=76) or offline (n=84) group. Both groups followed an identical structured six-week exercise program. Pain levels were assessed using the VAS at baseline, three weeks, and six weeks. Randomization was concealed using the Sequentially Numbered, Opaque, Sealed Envelopes (SNOSE) method. Data were analyzed using independent t-tests and repeated measures ANOVA. The study was approved by the Institutional Ethics Committee of Teerthanker Mahaveer University (Approval No.: PM/ETHICAL/PT/2023/004). Trial registration was not applicable. Results: Both groups demonstrated significant reductions in VAS scores over six weeks (p<0.0001). The offline group showed a significantly greater reduction at the third week (p=0.02) and sixth week (p<0.001) compared to the online group. At six weeks, the mean VAS reduction was 5.48 points in the offline group versus 5.03 points in the online group. Conclusion: Both online and offline group exercise programs effectively reduced pain among individuals with knee OA. However, offline programs resulted in faster and more substantial pain relief, suggesting that in-person supervision may enhance early clinical outcomes.